A longitudinal analysis of the relationship between serum uric acid and residual renal function loss in peritoneal dialysis patients. Issue 1 (1st January 2020) - Yang, Chiehlun; Ma, Xinxin; Zhao, Wenbo; Chen, Yanru; Lin, Hongchun; Luo, Dan; Zhang, Jun; Lou, Tanqi; Peng, Yu; Peng, Hui
Abstract: Background: Hyperuricemia occurs frequently in patients with continuous ambulatory peritoneal dialysis (CAPD). This study aimed to evaluate the impact of serum uric acid (UA) over time on residual renal function (RRF) loss in a cohort of patients with CAPD. Methods: A total of 201 patients who started CAPD therapy between January 1, 2008 and April 30, 2016 were included in this single-center, retrospective cohort study. All patients were followed up until December 31, 2016. The median follow-up time was 23.43 ± 16.60 months. RRF loss was represented as the time to anuria. Results: Eighty-six patients developed anuria within 5 years. Multivariate Cox regression analysis showed that time-averaged serum UA and peritonitis were independent risk factors for RRF loss, while weekly Kt/V urea was a protective factor. Cox proportional hazard regression models showed that both patients with time-averaged uric acid (TA-UA) < 6.77 mg/dL [hazard ratio (HR) = 1.165, 95% confidence interval (CI) 1.054–1.387; p < 0.05] and those with TA-UA≥ 7.64 mg/dL (HR = 1.184, 95% CI 1.045–2.114; p < 0.05) had a higher risk of RRF than those with TA-UA in the range of 6.77–7.64 mg/dL. Penalized spline smoothing also showed a U-shaped relationship between continuous UA and RRF loss. Conclusion: The present study demonstrated that both high and low serum UA over time were associated with RRF loss in patients with CAPD.